Scarf Pin Inhalation in Young Girls: Atypical Type of Foreign Body Inhalation - Muhammad Arshad, Muhammad Umer, Muhammad Kashif,Mohammad Aslam Ch, Muhammad Arshad, Muhammad Umer, Muhammad Kashif,Mohammad Aslam Ch (Journal of Rawalpindi Medical College, 2019)
Background: To study the causes and pattern of scarf pin inhalation in young girls Methods: In this descriptive study patients, with a history of scarf pin inhalation, were included. A detailed history of onset, duration and time between inhalation and presentation to hospital was taken. Comprehensive physical examination was carried out in all patients to recognize any cardio respiratory complications. The precise anatomical location and position of the pin was determined by chest x-ray. All the procedures were performed under general anaesthesia after proper preoperative assessment. Bronchoscope was introduced by classic technique under standard anaesthetic monitoring assisted ventilation. The scarf pin was visualized and retrieved by grasping forceps of appropriate length and design. Repeat rigid bronchoscopy was done, where required. Chest x-ray was repeated in all patients to see any complications. Patients were discharged in stable condition after 24 of surgery. Results: Total 33 female patients were included in study with history of pin inhalation. Mean age (years) in the study was 16.74+2 ranging in age from 12 to 30 years. The most frequent presenting complaints were cough and foreign body sensation in throat. Out of 33 cases, 12(36.36%) were in left main bronchus, 8 (24.24%) were in right main bronchus and 6 (18.18%) scarf pin were impacted in trachea. Conclusion: Scarf pin inhalation is a life threatening condition which is more common in muslim females due to hijab. Scarf pin inhalation in females can be prevented by increasing public awareness, prohibiting them from placing pin in their mouth